CD166/ALCAM mediates proinflammatory effects of S100B in delayed type hypersensitivity - Bauer, Rüdiger von; Oikonomou, Dimitrios; Sulaj, Alba; Mohammed, Sawsan; Hotz-Wagenblatt, Agnes; Gröne, Hermann-Josef; Arnold, Bernd; Falk, Christine Susanne; Luethje, Dorit; Erhardt, Axel; Stern, David M.; Bierhaus, Angelika; et al. (The journal of immunology, 2013)
Promiscuity of pattern recognition receptors, such as receptor for advanced glycation end products (RAGE), allows for a complex regulatory network controlling inflammation. Scavenging of RAGE ligands by soluble RAGE treatment is effective in reducing delayed-type hypersensitivity (DTH), even in RAGE−/− mice by 50% (p < 0.001). This has led to the hypothesis that molecules scavenged by soluble RAGE bind to receptors other than RAGE. This study identifies CD166/ALCAM (ALCAM) as a close structural and functional homolog of RAGE, and it shows that binding of S100B to CD166/ALCAM induces dose- and time-dependent expression of members of the NF-κB family in wild type (WT) and RAGE−/− mouse endothelial cells. Blocking CD166/ALCAM expression using small interfering RNA completely inhibited S100B-induced NF-κB activation in RAGE−/−, but not in WT cells. The in vivo significance of these observations was demonstrated by attenuation of DTH in WT and RAGE−/− animals pretreated with CD166/ALCAM small interfering RNA by 50% and 40%, respectively (p < 0.001). Experiments in ALCAM−/− animals displayed an only slight reduction of 16% in DTH, explained by compensatory reciprocal upregulation of RAGE in animals devoid of CD166/ALCAM, and vice versa. Consistently, ALCAM−/− mice, but not WT mice treated with RAGE small interfering RNA show a 35% reduction in DTH, and ALCAM−/− RAGE−/− double-knockout mice show a 27% reduction in DTH reaction. Thus, S100B is a proinflammatory cytokine bridging RAGE and CD166/ALCAM downstream effector mechanisms, both being compensatory upregulated after genetic deletion of its counterpart.